Strengthening Students’ Character and Social Development through Islamic Values Internalization in Aqidah Akhlak Learning - Rasyidin; Fransisco Chaniago (WISE Pendidikan Indonesia, 2026)
This study examines the role of Islamic values internalization through Aqidah Akhlak learning in strengthening students’ character and social development within madrasah education. A qualitative descriptive design was employed at Al-Khairiyah Private Madrasah Tsanawiyah in Jambi City, Indonesia, involving 20 purposively selected participants comprising one school principal, two Aqidah Akhlak teachers, and seventeen students. Data were collected through observation, semi-structured interviews, and documentation and analyzed using the Miles and Huberman interactive model involving data reduction, data display, and conclusion drawing. The findings identified four interconnected patterns of Islamic values internalization: value integration through learning activities, teacher role modeling, religious habituation, and the development of a religious school culture. These practices functioned as continuous educational mechanisms that reinforced students’ moral understanding and behavioral adaptation. The internalization process was influenced by differences in students’ awareness, peer influence, social media exposure, and limited parental support. Overall, these practices contributed to the development of discipline, responsibility, politeness, religious awareness, empathy, cooperation, and positive social interaction among students. The findings demonstrate that the internalization of Islamic values through Aqidah Akhlak learning integrates moral knowledge, character formation, and social development into madrasah educational practices.